Tracce agostiniane negli scritti di Husserl - Ales Bello, Angela (Bollettino Filosofico, 2024)
The aim of my paper is to examine the presence of certain philosophical arguments of Augustine of Hippo in Husserlian phenomenology. This investigation is made possible by the citation of Augustine’s famous saying, “noli foras te ire, in interiore homine habitat veritas”, in three of Husserl's works concerning the transcendental reduction, the theme of time, and ethical-religious questions. In addition to these three fundamental aspects of phenomenological analysis, one must also consider philosophical anthropology and the relationship between the Divine and the human being. There are numerous traces of Augustine in Husserl’s analyses: some are explicitly referenced, while others can be uncovered through a comparative study of the two thinkers’ works. The connection with Augustine is therefore particularly significant in relation to theories of knowledge, anthropology, and Husserl’s unique “metaphysics”. Keywords: Ethical-Religious Questions, Interiority, Time, Transcendental Reduction, Truth